Supporting Students With Co-Occurring Language and Behavioral Deficits in the Classroom. (March 2020) - Chow, Jason C.; Walters, Sharon; Hollo, Alexandra
For all children and youth, language underpins success in academic, social, and behavioral interactions. For students with language deficits, even seemingly simple tasks can be challenging and frustrating. Perhaps not surprising, children with language deficits often exhibit high rates of problem behavior, and children with behavior disorders tend to have low language ability. Because language and behavior are fundamental to success in school, teachers need to understand the comorbidity of these challenges, recognize signs that a student may be struggling with language delays, and have strategies to support students who struggle with behavior and language. In the present article, we (a) introduce and address co-occurring language and behavioral deficits, (b) overview common types of language difficulties in school, and (c) provide classroom management and instructional strategies to support students with these dual deficits.